The Influence of the Value Relevance of Accounting Information, Investment Decisions on Company Value and Inflation with Dividend Policy as an Intervening Variable in Banking Companies in 2016-2020 - Tetty Tiurma Uli Sipahutar; Tiffany Patricia; Stevany Ang; Ria Manurung (Britain International for Academic Research (BIAR) Publisher, 2024)
This research is motivated by an increase in the average book value every year for the last five years in banking companies, which is caused by stable regional inflation that has occurred in the last decade and the high value of dividends given by companies to investors. The increase in the company's book value was due to the relevance of the value of accounting recording information within the company and investment value decisions made by banking companies in developing their companies as well as the increase in the number of investors. The aim of this research is to analyze the influence of the value relevance of accounting information, investment decisions on company value and inflation with dividend policy as an intervening variable in banking companies in 2016-2020. This research uses quantitative research. Data collection was carried out using secondary data from financial reports. The respondents in this research were 35 banking companies using a purposive sampling method. The relevance of the value of accounting information has a negative and significant effect on company value with dividend policy as an intervening variable. Investment decisions have a negative and insignificant effect on company value with dividend policy as an intervening variable. The relevance of the value of accounting information has a positive and significant effect on inflation with dividend policy as an intervening variable. Investment decisions have a negative and significant effect on inflation with dividend policy as an intervening variable.